Ethanolamines as Corrosion Inhibitors for Zinc in Sulfamic Acid - Champaneri, V.A.; Vashi, R.T. (Asian Journal of Chemistry, 2010)
The corrosion of zinc in sulfamic acid containing ethanolamines has been studied. In plain acid, corrosion increases with concentration of acid and with the temperature. At constant acid concentration, the inhibition effeciency of ethanolamines increases with inhibitor concentration. Similarly, at constant inhibitor concentration, the inhibition efficiency increases with the increase in concentration of acid. Ethanolamines show excellent inhibitor in all acid concentration as well as at all inhibitor concentration at 301 K. The efficiency of the inhibitors decreases in the order: ethanolamine > diethanolamine > triethanolamine. As temperature increases, percentage of inhibition decreases. The mode of inhibition action appears to be chemisorption since the anodic and cathodic regions through general adsorption following the Langmuir isotherm. Anodic and cathodic galvanostatic polarization curves show little anodic but significant cathodic polarization.